2008
DOI: 10.1007/s10067-008-1035-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of anti-cyclic citrullinated peptide antibodies for rheumatoid arthritis in patients with active lung tuberculosis

Abstract: This study was intended to evaluate the utility of anti-cyclic citrullinated peptide antibodies (second generation, anti-CCP2) as a diagnostic marker for rheumatoid arthritis (RA) in patients with active tuberculosis. Among 89 patients with active tuberculosis, anti-CCP2 was detected in six (6.7%), and three of these (3.4%) were strongly positive for anti-CCP2. The positive rate of anti-CCP2 in patients with newly diagnosed RA was 82.1% (87 of 106 cases), while the rate in healthy control subjects was 0.4% (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Anti-CCP has also been shown to detect early RA in patients with active tuberculosis [105]. For SLE patients with chronic destructive/deforming arthritis and patients with pulmonary tuberculosis who are anti-CCP positive, the ratio of anti-CCP to unmodified arginine-containing peptide (CAP) differs between these and RA patients, providing a means for differential diagnosis [85, 106–108].…”
Section: Resultsmentioning
confidence: 99%
“…Anti-CCP has also been shown to detect early RA in patients with active tuberculosis [105]. For SLE patients with chronic destructive/deforming arthritis and patients with pulmonary tuberculosis who are anti-CCP positive, the ratio of anti-CCP to unmodified arginine-containing peptide (CAP) differs between these and RA patients, providing a means for differential diagnosis [85, 106–108].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Mori et al (12) reported that anti-CCP antibodies were positive in 6 of 89 patients with active pulmonary TB (6.7%) and 0.4% in the control group (n=267). Although anti-CCP levels were higher compared to healthy controls, it was suggested that anti-CCP levels could be used in the early diagnosis of RA in patients with active TB.…”
Section: Discussionmentioning
confidence: 86%
“…Although anti-CCP levels were higher compared to healthy controls, it was suggested that anti-CCP levels could be used in the early diagnosis of RA in patients with active TB. It was also stated that anti-CCP might become positive years before RA manifestations and these patients might develop RA at a later time period (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, anti-CCP antibodies have not been previously described in patients with arthritis induced by BCG. 29,30 This can be explained by anti-CCP antibody induction and maintenance of an immune response to chronic granulomatous inflammatory tissue rather than a direct response to the Mycobacterium. 27,28 Nevertheless, positive anti-CCP antibody has been demonstrated in patients with active tuberculosis in 6.7% to 37% of cases.…”
Section: Discussionmentioning
confidence: 99%